2005
DOI: 10.1109/tns.2005.856910
|View full text |Cite
|
Sign up to set email alerts
|

Planar edgeless silicon detectors for the TOTEM experiment

Abstract: Abstract-Silicon detectors for the Roman Pots of the the large hadron collider TOTEM experiment aim for full sensitivity at the edge where a terminating structure is required for electrical stability. This work provides an innovative approach reducing the conventional width of the terminating structure to less than 100 m, still using standard planar fabrication technology. The objective of this new development is to decouple the electric behavior of the surface from the sensitive volume within a few tens of mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…The current terminating structure, consisting of two p+ rings, was located in the area adjacent to the sensitive cut. The proper operation of the CTS was confirmed using measurements of I-V characteristics of full size detectors (with an area of 8 cm 2 ), which showed that the current in the sensitive bulk is actually a bulk generation current that is about four orders of magnitude smaller than the CTR current [5]. Statistics of the bulk current from over 200 detectors (Fig.…”
Section: Experimental Samples and Techniquesmentioning
confidence: 86%
See 3 more Smart Citations
“…The current terminating structure, consisting of two p+ rings, was located in the area adjacent to the sensitive cut. The proper operation of the CTS was confirmed using measurements of I-V characteristics of full size detectors (with an area of 8 cm 2 ), which showed that the current in the sensitive bulk is actually a bulk generation current that is about four orders of magnitude smaller than the CTR current [5]. Statistics of the bulk current from over 200 detectors (Fig.…”
Section: Experimental Samples and Techniquesmentioning
confidence: 86%
“…These two assumptions are actually equivalent since both postulate that the hole current at the cut edge is dominant. Combination of (5) and (6) gives a linear rise of the total currentjs and the electric field E s along the cut is: div(jJ= ge-'Ie div(hJ = gh, (4) ge=gh jh = gh(d -x) (5) je = (ge -'IJx (6) where W: is the specific distance for E z dissipation. W z can be estimated as the detector thickness, d, within which the detector edge effects are dissipated.…”
Section: Experimental Samples and Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…For reducing the termination area and being compatible with the standard planar detector, a current terminating structure (CTS) is proposed [8], [9]. The Current Terminating Ring (CTR) collects the current generated at the highly damaged region close to the edge, where it is cut, thereby avoiding its diffusion into the sensitive volume.…”
mentioning
confidence: 99%